Pedagogical Support for Ukrainian War-Affected Children: Future Teachers’ Readiness to Work in Crisis. Comparative Analysis of Research Results in Ukraine and Poland - Budnyk, Olena; Sajdak-Burska, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The significance of the defined issue of psychological and pedagogical support of children affected by the russian military aggression in Ukraine (2022-2023) is substantiated in the article based on the analysis of scientific literature and monitoring of media resources. Several types of crimes against Ukrainian children are presented, such as kidnapping, deportation, forced russification, etc. The questionnaire has been developed and the results of the survey of Ukrainian and Polish students (prospective teachers) with pedagogical experience of dealing with temporarily displaced persons due to the war are presented. Typical challenges they face from a psychological and pedagogical perspective have been identified: psycho-emotional worries of students; communication problems in educational activities; homesickness (which can sometimes be accompanied by depression, sleep disorders and high levels of anxiety); adaptation to new surroundings; periodic air raids, military operations (like those in Ukraine); low motivation to study, lack of interest; double workload for students in Poland (studying in Ukrainian schools online and in foreign schools offline), etc. Based on the qualitative and quantitative analysis of the questionnaire findings, recommendations for the professional training of future teachers to deal with children in crisis, in particular children with war trauma, are proposed. The author emphasizes the importance of developing infomedia literacy, critical thinking, future teachers’ skills in creating a media lesson, and media hygiene as the use of electronic communication and distance learning is a priority in the post-war period and requires information safety from ideological manipulations. Considerable emphasis is given to the development of teacher resilience as the capacity of the human psyche to recover, increase stress resistance, and prevent burnout when dealing with students who have suffered from russian aggression or are experiencing other crisis conditions